Analysis of Green Open Space Policy in Urban - Diah Putri Hasanah; Lukman Arif (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This research aims to analyze the implementation of Regional Regulation Policy Number 1 of 2020 concerning Regional Spatial Planning in the development of Green Open Space in Probolinggo City. This investigation utilizes qualitative research methodology, employing a case study approach. Data gathering involves observation, interviews, and documentation techniques. The results of the study show that the implementation of regional spatial plan policies in the provision of RTH in Probolinggo City has not been implemented optimally which does not achieve the target in the 2019-2024 RPJMD. This is because, in the aspect of resources, namely human resources and budget, there still needs to be an addition in optimizing the RTH development and preservation program. In addition, economic and social conditions also need government attention because the people of Probolinggo City still do not care about the environment.